Stanovení křivek citlivosti pro litograf s gaussovským svazkem - Šuľan, Dušan (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2014)
Předkládaná práce se zabývá procesem tvorby struktur pomocí elektronové litografie. Základním zaměřením práce je stanovení křivek citlivosti rezistu PMMA pro elektronový litograf Vistec EBPG 5000+ ES. Křivky citlivosti jsou stanoveny pro různé vývojky, doby vyvolávání a hloubky rezistu. Z těchto křivek jsou poté určeny citlivosti a kontrasty pro danou soustavu rezist-vývojka. Následně jsou křivky citlivosti aplikovány na korekce proximity efektu u reálných struktur, konkrétně u difrakčních periodických mřížek a potom vyhodnoceny.

This work deals with technological process of structures creating by using of electron beam lithography. The main focus of the work is contrast curves of PMMA resist determination for electron beam lithography system Vistec EBPG 5000+ ES. Contrast curves are determined for different developers, developing times and the depths of resist. Sensitivity and the contrast of resist are determined from these contrast curves for each resist-developer system. Sensitivity curves are applied to the proximity effect correction on real structures, specifically the periodic diffraction gratings and then they are evaluated.
The contrast curves determination for e-beam writer with Gaussian beam
Keywords: Elektronová litografie; elektronový litograf; křivka citlivosti rezistu; PMMA.; Electron-beam lithography; Electron-beam writer; resist contrast curve; PMMA